Archaeometry – Analyzing the Cultural Heritage - Willem B. Stern (CHIMIA, 2001)
Archaeometry is an interdisciplinary field of research, where the studied object stems from archaeological, cultural or historical domains whereas the approach of investigation is based on (natural) science. In the present overview the main focus is on case studies and non-destructive techniques. X-ray fluorescence and diffraction studies on ceramics, coin alloys, glass, man-made and natural gemstones, and objects of fine art prove that material analysis may contribute to insights in questions of authenticity and origin, but also in ancient technologies e.g. of coinage.